Pregnant Women's Perception about HIV/AIDS with the Implementation of HIV Tests - Ayuk Widiani; JDM Sriwitati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
One of the infectious diseases that is being talked about is HIV / AIDS, an infectious disease caused by infection with the Human Immunodeficiency Virus. The number of new cases of HIV / AIDS in Indonesia tends to fluctuate. The purpose of this study was to determine the relationship between perceptions of pregnant women about HIV / AIDS with the implementation of the HIV test. The design of this study was questionnaire based survey with cross sectional approach, to determine the factors that influence the implementation of HIV test in pregnant women. The population in this study were all pregnant women in the working area of Puskesmas II Denpasar Barat, amounting to 573 people and a sample of 82 people. The sampling technique used was consecutive sampling. Chi Square statistical test and Logistic Regression were applied for bivariate and multivariate analysis respectively. The results showed that there was a relationship between the perception of vulnerability of pregnant women about HIV / AIDS and the implementation of the HIV test (p = 0.002), there was a relationship between the perception of the severity of pregnant women and the HIV test (p = 0.019), HIV test (p = 0.006), there was a relationship between the perception of obstacle for pregnant women and the implementation of the HIV test (p = 0.009), the most dominant variable associated with the implementation of the HIV test was perception of vulnerability (p = 0.004, OR: 5.885, 95% CI 1,776-19,493). There is significant relationship between perception with HIV testing and vulnerability perception is the most dominant variable affecting HIV testing. The results of this study it is recommended to increase health promotion related to the implementation of HIV testing and its benefits so that pregnant women are willing to carry out HIV testing.